IMPACT OF URBANIZATION OF SUBURBAN AREA ON WATER RELATION IN THE SMALL CATCHMENTS - Jolanta Kanclerz (Inżynieria Ekologiczna, 2016)
This paper presents results of analysis focused on impact of urbanization of Poznań suburban area on water relation for Doływ spod Lusówka and Przeźmierki catchments during 1936–2011. Both catchments are located in municipalities which recently showing sharp growth in urban area. Analysis of changes in land use for studied catchments showed almost 5-fold increase in urban area for Dopływ spod Lusówka and 10-fold for Przeźmierka. As a consequence of land sealing increase in amounts of effective precipitation was observed that led to fast runoff of rain waters and almost double flow in watercourses.